2016
DOI: 10.1007/s11657-016-0292-1
|View full text |Cite|
|
Sign up to set email alerts
|

Unmet needs and current and future approaches for osteoporotic patients at high risk of hip fracture

Abstract: SummaryThis review provides a critical analysis of currently available approaches to increase bone mass, structure and strength through drug therapy and of possible direct intra-osseous interventions for the management of patients at imminent risk of hip fracture.PurposeOsteoporotic hip fractures represent a particularly high burden in morbidity-, mortality- and health care-related costs. There are challenges and unmet needs in the early prevention of hip fractures, opening the perspective of new developments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 123 publications
0
55
0
Order By: Relevance
“…The gap between the initiation of antiresorptive or anabolic osteoporosis therapies, often only prescribed after an initial fragility fracture, and the time to fracture risk reduction with these treatments means that these patients remain at a high risk for a hip fragility fracture. Thus, given the limitations of existing methods, there is a significant need for new approaches to reduce hip fractures …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The gap between the initiation of antiresorptive or anabolic osteoporosis therapies, often only prescribed after an initial fragility fracture, and the time to fracture risk reduction with these treatments means that these patients remain at a high risk for a hip fragility fracture. Thus, given the limitations of existing methods, there is a significant need for new approaches to reduce hip fractures …”
mentioning
confidence: 99%
“…Alternate surgical approaches that have gained interest recently, in part because they are not dependent on patient compliance, include femoral bone augmentation procedures aimed at increasing femoral strength . In support of these approaches, biomechanical studies have evaluated femoral augmentation using non‐resorbable polymethyl methacrylate (PMMA), silicone rubber, or prophylactic hardware .…”
mentioning
confidence: 99%
“…The retrospective analysis on a subgroup of patients referred to such a service within the hospital soon after the fracture, demonstrate that even in a Mediterranean country such as Italy almost a half of patients experiencing a hip fracture is severely vitamin D deficient and only less than 10% have serum 25(OH)D levels above 30 ng/ml, which is considered the threshold to be achieved in subjects at high risk for fracture (15). Since vitamin D sufficiency is required to begin osteoporotic therapy, given the high prevalence of vitamin D deficiency in elderly people throughout the year even in Mediterranean countries such as Italy, elders experiencing a major osteoporotic fracture such a hip fracture or at high risk for fracture should receive vitamin D supplementation straight away, despite waiting for the determination of serum 25(OH)D levels (7,(15)(16)(17). In the retrospective survey, only 15.0% of patients received cholecalciferol at the time of the fracture event.…”
Section: Discussionmentioning
confidence: 99%
“…only 31% of included patients returned to their pre-injury walking ability. To address the issue of hip fragility fracture prevention, a new medical device, Y-STRUT ® (Hyprevention, France), was developed to be implemented in the proximal femur by minimally invasive surgery [22,23]. Biomechanical tests on human osteoporotic femurs showed that the implantable medical device, placed in the proximal femur, increases the bone fracture load and energy to fracture in case of fall without modifying or worsening the nature of the fracture [24].…”
Section: Introductionmentioning
confidence: 99%